Scalar field theory at finite temperature in D=2+1 - Ananos, G. N. J. [UNESP] (American Institute of Physics (AIP), 2006)
We discuss the phi(6) theory defined in D=2+1-dimensional space-time and assume that the system is in equilibrium with a thermal bath at temperature beta(-1). We use the 1/N expansion and the method of the composite operator (Cornwall, Jackiw, and Tomboulis) for summing a large set of Feynman graphs. We demonstrate explicitly the Coleman-Mermin-Wagner theorem at finite temperature.